THE URGENCY OF GOOD FAITH FROM THE PERSPECTIVE OF SADDUD DZARI’AH THEORY (A STUDY OF DECISION NO. 426/Pdt.G/2021/PA.JS) - Silvana, Sindy Siska (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
This study examines the application of the principle of good faith in a Sharia insurance dispute, as presented in Case No. 426/Pdt.G/2021/PA.JS and evaluates its legal relevance from the perspective of Saddud Dzari’ah. Using a qualitative normative-empirical method through the examination of judicial decisions, policy terms, and Sharia insurance regulations, the research finds that the Plaintiff provided inaccurate information concerning medical history, other insurance ownership, and domicile. These inaccuracies constituted a breach of the principle of utmost good faith (uberrimae fidei), giving the Defendant legal grounds to rescind the policy and deny the claim in accordance with applicable laws and contract provisions. Normatively, such a violation at the pre-contractual stage should have led to the rejection of the lawsuit in its entirety. However, the judges applied the Saddud Dzari’ah principle to realize substantive justice by ordering the return of premiums to prevent harm and maintain fairness and proportionality of rights and obligations. The study highlights the need for stricter verification and auditing standards for participant data in Sharia insurance. It also shows that Saddud Dzari’ah provides a normative and argumentative basis for harmonizing legal certainty and fairness in dispute resolution. Additionally, the research reveals weaknesses in the fact-finding process, emphasizing the importance of a more proactive and rigorous judicial approach to ensure thoroughly examined material facts and a fair judgment.